Chiral Majoranas morphing into corner states in ordinary QAH/SC systems - Pupim, Lucas Vieira (2022)
Today, the realization of Majorana states is one of the most sought after results in condensed matter. The focused attention on this issue comes from the desire of using these states to create robust topological quantum computers. This quest may be accomplished through many paths as there are several proposals for Majorana platforms. One of the most recent paths involves high-order topological superconductivity. Here, we study a junction formed by a quantum anomalou Hall system and an s-wave superconductor, known for hosting chiral Majorana edge states, and show that by tuning parameters this system can exhibit a 2nd-order phase with Majorana corner states. We model this system via a single Dirac cone describing the surface state of a 3D topological insulator in close proximity to a superconductor. We characterize this system through the lens of the symmetries of the Hamiltonian and electronic transport within the non-equilibrium Greens function formalism. Our results extend the previous analysis from Qi et al. (1), which only found first-order topological phases in a similar system. We show that four Majorana corner states can emerge our QAH-SC setup within the previously proposed chiral phase. In addition, we conjecture that these corner states are correlated to the formation of domain walls in the pairing function due to the presence of boundaries (edges and corner). We also show that these states are protected by a pair of magnetic mirror symmetries. Moreover, in the absence of a topological invariant to characterize this high-order phase, we determine an effective phase diagram for our finite system by looking at the zero-bias conductance peaks. Through a characteristic e2/h zero-bias peak and looking at the lowest energy states wave-function, we find a wide region in the (μ, Δ) parameter space corresponding to the 2nd-order phase with Majorana corner states. This work extends our knowledge not only about this particular model Hamiltonian but also about how we can find high-order topological superconductor phases.